The Effect of Business Capital and Product Innovation on Business Performance in Human Resource Management - Ambarwati Ambarwati; Indah Purwanti; Linda Yosiawati; Tony Arief Budiman; Noor Ritawaty (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Business capital and product innovation are key factors influencing business performance, especially within the scope of human resource management. However, businesses often face challenges in optimizing both simultaneously. This study aims to analyze the effect of business capital and product innovation on business performance through human resource management approaches. The study employs a quantitative method with an explanatory research design. Data were collected from 69 small and medium-sized enterprises (SMEs) in Indonesia using structured questionnaires. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Business capital and product innovation significantly influence business performance. Business capital also strongly correlates with product innovation as a mediator. Product innovation improves business performance by 39.5%, while business capital enhances product innovation by 71%, highlighting the importance of business capital in supporting innovation. Business capital is not only a primary resource but also a driver of innovation, directly impacting business performance. Optimizing business capital and product innovation is crucial in managing human resources effectively.